SMALL AND MEDIUM ENTERPRISES AS A MEANS TO PROMOTE ECONOMIC DEVELOPMENT STUDY THE ROLE OF SMALL AND MEDIUM ENTERPRISES IN JOB CREATION AND GROWTH - Kamit Saeed Awad (Scholars Digest Publishing, 2024)
The investigation intended to determine the degree to which small and medium sized companies in Iraq have grown and created jobs, as well as the role that small and medium sized companies play in increasing income per capita and decreasing unemployment. Descriptive analysis was employed, and questionnaires were distributed to the participants in the study of small and medium sized enterprises (180) in the Baghdad region. (169) questionnaires were retrieved, (8) questionnaires containing missing values and (11) questionnaires containing extreme values were deleted as suitable for analysis, and (150) were solved for the final total. The study found that the level of growth of small and medium enterprises in Iraq was associated with the arithmetic mean of (3,534) and moderately. In contrast, the average job creation and growth were associated with the arithmetic mean of (3,413). The study also showed that the study found that there was a significant relationship between the growth of small and medium enterprises in Iraq and the size of the employment creation and growth (access to financing from financial institutions, increase in per capita income, and reduction in unemployment).
Keywords: SMEs, economic development, job opportunities.